Kolaborasi Kelembagaan Dalam Mendukung Event Merti Desa Doplang - Bambang Guritno; Sapto Supriyanto; Hartoyo Hartoyo; Mudrik Abdullah (Universitas Maritim AMNI Semarang, 2023)
The concept of Collaborative Government as an alternative basis is considered capable of realizing the acceleration and implementation of Tourism Areas. Collaborative Governance as a new paradigm that is used to deal with various issues in a complex society, the paradigm that is meant is the basic principle of equal relations between stakeholders in the public, private and community sectors. It is also a process that involves various stakeholders who are related to the interests or achieve a goal. This study analyzes Collaborative Governance in Sustainable Tourism Management, especially in Doplang Village. Then, this study uses qualitative research methods. The results of the research on the Doplang Tourism Village, Bawen District, Semarang Regency, are a source of income for the local community with the level of tourists visiting tourist attractions and also increasing people's income.